Distance to clinic is a barrier to PrEP uptake and visit attendance in a community in rural Uganda. Issue 4 (29th April 2019) - Mayer, Christopher M; Owaraganise, Asiphas; Kabami, Jane; Kwarisiima, Dalsone; Koss, Catherine A; Charlebois, Edwin D; Kamya, Moses R; Petersen, Maya L; Havlir, Diane V; Jewell, Britta L
Abstract: Introduction: Geographic and transportation barriers are associated with poorer HIV‐related health outcomes in sub‐Saharan Africa, but data on the impact of these barriers on prevention interventions are limited. We estimated the association between distance to clinic and other transportation‐related barriers on pre‐exposure prophylaxis (PrEP) uptake and initial clinic visit attendance in a rural community in southwestern Uganda enrolled in the ongoing SEARCH study (NCT01864603). Methods: Community‐wide HIV testing was conducted and offered to adult (≥15 years) participants in Ruhoko. Participants were eligible for PrEP based on an empiric risk score, having an HIV‐discordant partner, or self‐referral at either the community health campaign or during home‐based testing from March to April 2017. We collected data from PrEP‐eligible households on GPS‐measured distance to clinic, walking time to clinic and road difficulty. A sample of participants was also asked to identify their primary barriers to PrEP use with a semi‐quantitative questionnaire. We used multivariable logistic regression to evaluate the association between transportation barriers and (1) PrEP uptake among PrEP‐eligible individuals and (2) four‐week clinic visit attendance among PrEP initiators. Results: Of the 701 PrEP‐eligible participants, 272 (39%) started PrEP within four weeks; of these, 45 (17%) were retained at four weeks. Participants with a distance to clinic of ≥2 km were less likely to start PrEP (aOR 0.34; 95% CI 0.15 to 0.79, p  = 0.012) and less likely to be retained on PrEP once initiated (aOR 0.29; 95% CI 0.10 to 0.84; p  = 0.024). Participants who were deemed eligible during home‐based testing and did not have the option of same‐day PrEP start were also substantially less likely to initiate PrEP (aOR 0.16, 95% CI 0.07 to 0.37, p  < 0.001). Of participants asked to name barriers to PrEP use (N = 98), the most frequently cited were "needing to take PrEP every day" (N = 18) and "low/no risk of getting HIV" (N = 18). Transportation‐related barriers, including "clinic is too far away" (N = 6) and "travel away from home" (N = 4) were also reported. Conclusions: Distance to clinic is a significant predictor of PrEP uptake and four‐week follow‐up visit attendance in a community in rural Uganda. Interventions that address geographic and transportation barriers may improve PrEP uptake and retention in sub‐Saharan Africa.